Digital Financial Literacy Moderates The Effect Of Financial Capability and Behavior on Financial Well-Being - Raihan Ramadhan Adriansya Putra; Endah Susilowati (Balance Vocation Accounting Journal, 2026)
This study was conducted to analyze the influence of financial capability and financial behavior on students’ financial well-being, as well as to assess the role of digital financial literacy as a moderating variable in these relationships. The research background stems from the increasing economic pressure experienced by Generation Z in Indonesia, particularly university students, who face low income, financial dependence on family, and high usage of digital financial services. The study employed a quantitative approach with an explanatory method, involving 98 undergraduate accounting students from three campuses of Universitas Pembangunan Nasional “Veteran.” Data were collected through questionnaires and analyzed using validity tests, reliability tests, classical assumption tests, and moderated regression analysis. The findings indicate that both financial capability and financial behavior significantly affect financial well-being. Digital financial literacy strengthens the effect of financial capability on financial well-being but does not strengthen the effect of financial behavior. These results highlight that proficiency in financial technology is a crucial factor that enhances the effectiveness of financial capability in supporting students’ financial well-being. This study provides empirical contributions regarding the importance of digital literacy in the modern financial ecosystem and its relevance for the development of financial education programs in higher education.